PERAN KEPEMIMPINAN TERHADAP PELAYANAN PUBLIK DIKANTOR KECAMATAN BATU AMPAR KABUPATEN KUTAI TIMUR - Sangka, Ibnu (PREDIKSI, 2014)
The purpose of this study was to determine the role of leadership to the public service at the office of the District Batu Ampar East Kutai Regency. Type of research including qualitative descriptive. The types of data used include primary data and secondary data, while data sources are taken from informen competent, among which sub-district with several people on staff whose job it is related to the research problem under study. While data collection techniques by observation, interviews, and documentation. Analysis of the data used is interactive model developed by Miles and Huberman.Â